DEVELOPMENT OF NUMERACY-BASED MATHEMATICS LEARNING MODULES ON FLAT SIDE SPACE BUILDING MATERIALS - Cahyani, Putri; Kurniawati, Naning; Ismanto, Ismanto (Nindikayla Institute, 2024)
The numeracy abilities of some students in class VIII SMP Plus Al Fatimah are still relatively low so special measures are needed, accompanied by ineffective teaching materials because there are too few material descriptions and the learning methods used are still conventional. So, it is necessary to develop teaching materials in the form of numeracy-based mathematics learning modules as a companion to the textbooks provided by the school. The research aims to develop a mathematics module on flat-sided geometric material that is valid and practical. The type of research used is Research and Development (R & D) with the ADDIE development method (analysis, design, development, implementation, and evaluation). The results of the development research obtained a numeration-based mathematics learning module on flat-sided geometric material with valid and practical categories. The learning module was declared valid by the validator, media experts scored 72.5% in the